Characterization of the Active Ingredients and Prediction of the Potential Anticolitis Mechanism of the Feng-Liao-Chang-Wei-Kang Capsule via Mass Spectrometry and Network Pharmacology - Tingting Liu; Zhijiang He; Witiao Lv; Liyun Deng; Xizhe Sun; Yanfei Chen (Journal of Analytical Methods in Chemistry)
The Feng-Liao-Chang-Wei-Kang (FLCWK) capsule is a nationally protected Chinese patent medicine for the treatment of colitis. However, the potential active components and the pharmacological mechanism underlying the anticolitis effect of the FLCWK capsule remain unclear. This study aimed to reveal the active ingredients and possible anticolitis mechanism of the FLCWK capsule using an integrated approach combining mass spectrometry and network pharmacology analysis. Ultra-performance liquid chromatography plus Q-Exactive Orbitrap tandem mass spectrometry (UPLC-Q-Exactive Orbitrap MS) was applied to identify the components of the FLCWK capsule. A network pharmacology study, including target gene prediction and functional enrichment, was applied to screen the active ingredients of the FLCWK capsule and explore its potential mechanism for the treatment of colitis. A total of 115 components were identified in the FLCWK capsule. Network pharmacology results showed that 46 of these compounds with good bioavailability and drug-likeness, such as 4′,5-dihydroxyflavone, pinostrobin, naringenin chalcone, apigenin, and morin, were selected as active ingredients. The active ingredients may act on 352 core protein targets, including EGFR, AKT1, PIK3R1, PIK3CB, and MAPK1, thereby modulating relevant pathways, such as MAPK and PI3K-Akt signaling pathways, and thus alleviating inflammation and intestinal damage in colitis. This study provided a useful approach to identify active components and the anticolitis mechanism of the FLCWK capsule and built up a reliable foundation for its clinical treatment.